2014
DOI: 10.3892/ijmm.2014.2008
|View full text |Cite
|
Sign up to set email alerts
|

miR-141 regulates TGF-β1-induced epithelial-mesenchymal transition through repression of HIPK2 expression in renal tubular epithelial cells

Abstract: Epithelial-mesenchymal transition (EMT) plays a critical role in embryonic development, wound healing, tissue regeneration, cancer progression and organ fibrosis. The proximal tubular epithelial cells undergo EMT, resulting in matrix-producing fibroblasts and thereby contribute to the pathogenesis of renal fibrosis. The profibrotic cytokine, TGF-β, is now recognized as the main pathogenic driver that has been shown to induce EMT in tubular epithelial cells. Increasing evidence indicate that HIPK2 dysfunction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 45 publications
8
44
0
Order By: Relevance
“…Overexpression of hsa-miR-141 has been shown to inhibit invasion and migration of breast cancer, colorectal cancer, and pancreatic cancer [10,21,22]. miR-141 was also found to regulate cancer cell growth and metastasis in lung cancer, liver cancer, colorectal cancer, gastric cancer, renal cancer, and prostate cancer [8][9][10][11][12][13]. In this study, we found that miR-141 was downregulated in breast cancer in tumor tissues compared with matched surrounding tissues.…”
Section: Effect Of Direct Anp32e Knockdown On Cell Proliferation Migmentioning
confidence: 54%
See 1 more Smart Citation
“…Overexpression of hsa-miR-141 has been shown to inhibit invasion and migration of breast cancer, colorectal cancer, and pancreatic cancer [10,21,22]. miR-141 was also found to regulate cancer cell growth and metastasis in lung cancer, liver cancer, colorectal cancer, gastric cancer, renal cancer, and prostate cancer [8][9][10][11][12][13]. In this study, we found that miR-141 was downregulated in breast cancer in tumor tissues compared with matched surrounding tissues.…”
Section: Effect Of Direct Anp32e Knockdown On Cell Proliferation Migmentioning
confidence: 54%
“…In BC cells, miR-141 targets EGFR, and inhibits its translation [7]. miR-141 was also found to regulate cancer cell growth and metastasis in lung cancer, liver cancer, colorectal cancer, gastric cancer, renal cancer, and prostate cancer [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As is well-known, EMT is a facilitator of tissue remodeling in many physiological progressions such as embryonic development, wound healing, tissue regeneration and organ fibrosis [65]. EMT is also a fatal early step in tumor metastasis formation by controlling the detachment of invasive cancer cells from the primary tumor [66].…”
Section: Mir-141 and Emtmentioning
confidence: 99%
“…In HIV-infected renal tubular epithelial cells, HIPK2 induced expression of pro-fibrosis markers via activating p53, TGF-β, and Wnt/Notch pathways [84]. Downregulation of HIPK2 leads to upregulated C-cadherin and decreases epithelial to mesenchymal transition [90]. These results suggest that HIPK2 is one of crucial regulators of kidney fibrosis by activating the upstream fibrosis signaling pathway.…”
Section: Pathophysiological Functions Of Hipk2mentioning
confidence: 99%